INSTRUMENTAL CAPACITY OF INTERNATIONAL BUSINESS IN MODERN CONDITIONS - Georgii Logvynskyi (Baltic Journal of Economic Studies)
The present study examines the institutional and instrumental capacity of international business in modern conditions. The purpose of the research is to identify and highlight the key institutional capabilities of the modern economy and the tools that can be used. Methodology. The study used general and special methods of scientific inquiry, including systems analysis, dialectical method, formal-logical method, structural-functional method, and various empirical methods. Results. The dynamics of new forms of international business functioning are established, characterised by features such as: a) virtual forms of operation (including through business platforms); application of modern technologies as the basis of functioning (including software, artificial intelligence); implementation of global and rapid networking via the Internet, etc. The instrumental capacity of international business in modern conditions is analysed, with a focus on Ukraine. The analysis identifies several key factors that necessitate the establishment of business platforms in Ukraine as instruments to achieve synergy in international business integration. These factors include globalisation processes, technological progress, integration, the need for legislative unification, the full-scale invasion of Ukraine by the Russian Federation, resource conservation, and economic growth. The paper identifies stakeholders that contribute to business development. It is noted the role of higher education institutions and civil society in business processes. The importance of academic partnerships and incubation programmes in business integration and co-operation is substantiated.